Study on the Use of the Ionic Liquid 1-butyl-3-methylimidazolium Hydroxide in Synthesis of Substituted 4-aryl-4H-chromenes - Thanh, Nguyen Dinh; Hai, Do Son; Dung, Tran Thi; Mai, Nguyen Thi; Dang, Le Hai (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 3, 2016)
Abstracts: An efficient and simple synthesis of substituted 2-amino-4 H -chromene-3-carbonitriles was developed by the one-pot and three-component reaction of a mixture of corresponding substituted benzaldehydes, resorcinol, and malononitrile in the presence of an ionic liquid, namely 1-butyl-3-methylimidazolium hydroxide, as catalyst at room temperature. The structure of synthesized compounds have been confirmed by using spectroscopic methods (IR, 1 H and 13 C NMR). Keywords: Ionic liquid, chromenes, pyrans, one-pot reaction, three-component reaction.